1978
DOI: 10.1152/ajpregu.1978.234.5.r209
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow and oxygen consumption in the newborn dog

Abstract: Cerebral blood flow (CBF), CBF responses to changes in arterial CO2 tension, and cerebral metabolic rate for oxygen (CMRO2) were measured in newborn dogs, by means of a modification of the Kety and Schmidt technique employing 133Xe. Mongrel dogs of 1-7 days of age were paralyzed and passively ventilated with 70% N2O and 30% O2. CBF was derived by analysis of paired serial 20-microliter samples of arterial and of cerebral venous blood from the superior sagittal sinus. At an arterial PCO2 of 36.9 +/- 3.7 Torr an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

1980
1980
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 0 publications
1
24
1
Order By: Relevance
“…The baseline regional CBF results and the increased flow to infratentorial regions in our study concurs with previous data in newborn dogs (9,(12)(13)(14). During the acute recovery phase the cerebral hemispheric and the combined cerebellar-brainstem flows increased 250 + 39 and 536 k 29% above baseline, respectively, with the percentage increase to the brainstem-cerebellum being significantly greater than that to the hemispheres ( p < 0.005).…”
Section: Discussionsupporting
confidence: 92%
“…The baseline regional CBF results and the increased flow to infratentorial regions in our study concurs with previous data in newborn dogs (9,(12)(13)(14). During the acute recovery phase the cerebral hemispheric and the combined cerebellar-brainstem flows increased 250 + 39 and 536 k 29% above baseline, respectively, with the percentage increase to the brainstem-cerebellum being significantly greater than that to the hemispheres ( p < 0.005).…”
Section: Discussionsupporting
confidence: 92%
“…Our results agree with those of Hernandez, et at. (9) who have demonstrated that the newborn dog's cerebral vascular responsiveness to CO2 is lower than that reported for adult dogs. The lack of an additive effect of Paco2 on the reduction of brain blood flow during hypotension suggests that hypocapnea may not produce an adultlike effect on neonatal cerebral circulation.…”
Section: Summary Speculationmentioning
confidence: 89%
“…This may explain the higher control flow values to this area, and the flow increase during hypoxia. Because mild and moderate hypoxia do not decrease O2 consumption (13,14,40,41), the brainstem should require higher levels of oxygen delivery and blood flow than the cortex and subcortex. However, we know of no studies of the regional differences in oxygen consumption during hypoxia in the fetus, newborn, or adult (1 1).…”
Section: Cardiac Output (Mlomin-'kg Body-')mentioning
confidence: 99%
“…Glucose recycling through lactate is an active mechanism in the primate fetus as well as in the young of other species. (Pediatr Res 118: 1984) or inferential data derived from infusion studies, tolerance tests (6,14), and stable isotope methodology (15). Previous investigations using the newly born baboon as a model for the study of neonatal energy metabolism suggest that this animal resembles the small-for-gestational-age human infant in terms of response to fasting and diminished body fat (19,20).…”
Section: Cardiac Output (Mlomin-'kg Body-')mentioning
confidence: 99%